Shadows reel [compact disc, unabridged] - Box, C. J. (Box, C. J. Joe Pickett novel., 2022)
Wyoming Game Warden Joe Pickett's job has many times put his wife and daughters in harm's way. Now the tables turn as his wife discovers something that puts the Pickett family in a killer's crosshairs.